2019
DOI: 10.1021/acs.est.8b04950
|View full text |Cite
|
Sign up to set email alerts
|

Sand Barriers around Latrine Pits Reduce Fecal Bacterial Leaching into Shallow Groundwater: A Randomized Controlled Trial in Coastal Bangladesh

Abstract: We evaluated the effectiveness of a sand barrier around latrine pits in reducing fecal indicator bacteria (FIB) leaching into shallow groundwater. We constructed 68 new offset single pit pour flush latrines in the Galachipa subdistrict of coastal Bangladesh. We randomly assigned 34 latrines to include a 50 cm thick sand barrier under and around the pit and 34 received no sand barrier. Four monitoring wells were constructed around each pit to collect water samples at baseline and subsequent nine follow-up visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Similarly, MAR source ponds had increased fecal load during the wet months, but the MAR systems successfully retained water with no to low risk fecal contamination. Shallow aquifers (<50 meters) often have low-level fecal contamination due to proximity to contamination sources such as pit latrines or intrusion from highly contaminated surface water bodies 27 . But the MAR systems were constructed at a safe distance from latrines and in areas with confined aquifers that had a top clay layer 14, 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MAR source ponds had increased fecal load during the wet months, but the MAR systems successfully retained water with no to low risk fecal contamination. Shallow aquifers (<50 meters) often have low-level fecal contamination due to proximity to contamination sources such as pit latrines or intrusion from highly contaminated surface water bodies 27 . But the MAR systems were constructed at a safe distance from latrines and in areas with confined aquifers that had a top clay layer 14, 21 .…”
Section: Discussionmentioning
confidence: 99%
“…A study by [12] reported that River Cauvery in India was loaded with coliform bacteria attributable to raw sewage. In a related study, high concentration microbes in drinking water sources located in close proximity to pit latrines (<20 m) were reported [13]. Additionally, construction Journal of Water Resource and Protection of residential houses in proximity or upstream to drinking water sources poses a threat to water contamination through leaching of contaminants.…”
Section: Characterization Of Drinking Water Sourcesmentioning
confidence: 97%
“…This is an eco-friendly and cost-effective way to line toilets in emergency situations. Naser et al (2019) reported a reduction of 27% E. coli and 24% thermotolerant coliform mean counts in pit latrines using a 50-cm thick sand barrier in coastal Bangladesh. Similarly, Banerjee (2011) demonstrated that clay enveloped around a leach pit toilet arrests the movement of chemical and bacteriological pollutants to a considerable extent.…”
Section: Pit Latrine Linersmentioning
confidence: 99%